Rancang Bangun Aplikasi Penilaian Kinerja Pegawai Berbasis Web Menggunakan Metode Scoring System Pada Badan Kepegawaian Daerah Provinsi Jawa Timur - Kurniawan, Johanes Aditya; Sulistiowati, Sulistiowati; Mastan, Ignatius Adrian (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Abstract: Regional Employment Board or BKD is owned by the government agency in charge of implementing the preparation and implementation of regional policies in the field of employment, and can be assigned to carry out the implementation of the authority delegated by the Government to as Representative of the Government in the framework of deconcentration. BKD East Java is an agency that specialized personnel in the area of East Java. To improve the quality of human resources, then carried out the assessment process, the assessment in question is the performance appraisal.Nowadays, the assessment using assessment form East Java BKD submitted in each city and distributed to agencies that have employees JFT. Long process of distributing a form of assessment, and the assessment results. In addition, BKD also need to collect data on JFT employees recommended for promotion. From each of the above problems, the biggest impact is employee development apparatus JFT will be hampered because the time is not in accordance with the schedule recommended training for employees. From the above problems made JFT employee performance evaluation application that can provide a good recommendation and report to the BKD East Java and related institutions with a quick and precise.Keywords: Application, Performance Appraisal, Human Resources